BUDAYA ORGANISASI MADRASAH TERHADAP KEDISIPLINAN DAN RELIGIUS SISWA MTs NEGERI 2 WONOSOBO - Mushokhifah -; Rifqi Muntaqo; Robingun Suyud El-Syam (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2022)
Madrasah organizational culture is a system of shared meaning held by members that distinguishes one madrasah from another. Madrasa Organizational Culture is carried out by all members in it, starting from Teachers, Employees, Students, to School Committees, because madrasas are a system. The application of Madrasah Organizational Culture is applied to students starting from students attending MTs Negeri 2 Wonosobo until they go home. This certainly affects the formation of discipline and religious students. This study used a qualitative method that is descriptive analysis in nature. The subjects of this study were the Head of Madrasah, Waka Curriculum, and Students of MTs Negeri 2 Wonosobo, while the object was the organizational culture of Madrasah Negeri 2 Wonosobo Madrasah. Data collection techniques using interviews, observation, and documentation studies with data analysis techniques are qualitative data analysis. The results of the research conducted by the author are: 1) The ideal concept of Madrasah Organizational Culture is one that fits the needs and also the real conditions that exist in the Madrasah. In this case MTs Negeri 2 Wonosobo adapts its Madrasah Organizational Culture to the situations and conditions in the school environment. 2) The efforts of the Madrasah head in shaping the organizational culture of the Madrasah can be structural and non-structural. 3) Factors Inhibiting the Formation of Madrasah Organizational Culture on Discipline and Religion of Students at MTs Negeri 2 Wonosobo, among others; First, the obstacles from students, namely the tendency of students to have a dynamic nature, because children of their age are indeed experiencing a period of development and exploration, which then creates a feeling of laziness. Second, the lack of support from parents. While the Supporting Factors include; First, awareness by all school members of the importance of Madrasah Organizational Culture. Second, full support from all stakeholders for the success of the program related to the madrasah organizational culture. Third, support from parents and society. Fourth, the use of the habituation method or habite rule. Fifth, a supportive environment. Sixth, facilities and infrastructure.